2013
DOI: 10.12659/msmbr.884019
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal alterations in different developmental stages of in vivo cryopreserved preimplantation murine embryos

Abstract: BackgroundThis study aimed to investigate the effects of vitrification and slow freezing on actin, tubulin, and nuclei of in vivo preimplantation murine embryos at various developmental stages using a Confocal Laser Scanning Microscope (CLSM).Material/MethodsFifty female mice, aged 4–6 weeks, were used in this study. Animals were superovulated, cohabitated overnight, and sacrificed. Fallopian tubes were excised and flushed. Embryos at the 2-cell stage were collected and cultured to obtain 4- and 8-cell stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Cell adhesions can be described as a functional extension of the actin cytoskeleton [ 65 ]. The cellular cytoskeleton may have a significant role in determining post-dehydration and post-thaw cell viability, thanks to its interaction with the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Cell adhesions can be described as a functional extension of the actin cytoskeleton [ 65 ]. The cellular cytoskeleton may have a significant role in determining post-dehydration and post-thaw cell viability, thanks to its interaction with the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The have been no similar studies on the effect of nicotine and subsequent supplementation of TRF. However, studies on actin and tubulin in cryopreserved embryos by the slow freezing method have shown that the procedure caused damage to actin and tubulin [ 38 ]. Whether the nature of the damage caused by cryopreservation is similar to that of nicotine warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been established that many factors are likely to influence the outcome of IVF, such as the adverse roles of nicotine [18] and the methods of preservation of frozen embryos [19], the effects of endometriosis on the results of IVF are currently controversial. Therefore, the aim of the present study was to retrospectively assess the efficacy of NC endometrial preparation for FET in women with severe endometriosis.…”
Section: Discussionmentioning
confidence: 99%